2008
DOI: 10.1007/s11199-008-9414-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Voices in Hong Kong English Textbooks—Some Past and Current Practices

Abstract: This paper seeks to investigate whether recent improvements in the status of women in Hong Kong are reflected in patterns of gender representation in Hong Kong secondary English textbooks. A comparison of ten recently published books which are currently in use with ten published in the late 1980s/early 1990s and no longer in use revealed that women appeared more frequently in the former, and that greater use was made of gender-inclusive pronouns and the neutral address title Ms. Nevertheless some writers, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 23 publications
5
68
3
1
Order By: Relevance
“…There is some evidence that in more recent years awareness of sexist issues has increased, and the representation of men and women in textbooks has become more balanced. For example Clarkson's (1993) study of Australian mathematics textbooks found that 45% of people depicted were male compared to 39% female, and Lee and Collins' (2008) comparison of Hong Kong English-language textbooks published preand post-1996 found a significant reduction in the numerical dominance of male characters, both in terms of character types and frequency.…”
Section: Omissionmentioning
confidence: 99%
“…There is some evidence that in more recent years awareness of sexist issues has increased, and the representation of men and women in textbooks has become more balanced. For example Clarkson's (1993) study of Australian mathematics textbooks found that 45% of people depicted were male compared to 39% female, and Lee and Collins' (2008) comparison of Hong Kong English-language textbooks published preand post-1996 found a significant reduction in the numerical dominance of male characters, both in terms of character types and frequency.…”
Section: Omissionmentioning
confidence: 99%
“…One of the outstanding studies is Lee and Collins (2008) who intended to find out whether during the gender bias elimination following passing of the Sex Discrimination Ordinance in 1995, the current Hong Kong English language school textbooks have evolved in terms of sexism or not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still, as Bauer, Holmes, and Warren (2006) claim, "Ms is frequently interpreted as title for divorced, separated or widowed woman" (p. 164). Lee and Collins (2008) state that examples of male firstness occur in nouns (e.g. Harry and Holly), possessive nouns (e.g., Harry and Holly's first day at school), subject and object pronouns (e.g., He is or him/her.…”
Section: Gender-neutralmentioning
confidence: 99%